2022
DOI: 10.1007/s12274-022-4647-1
|View full text |Cite
|
Sign up to set email alerts
|

Transport receptor occupancy in nuclear pore complex mimics

Abstract: Nuclear pore complexes (NPCs) regulate all molecular transport between the nucleus and the cytoplasm in eukaryotic cells. Intrinsically disordered Phe-Gly nucleoporins (FG-Nups) line the central conduit of NPCs to impart a selective barrier where large proteins are excluded unless bound to a transport receptor (karyopherin; Kap). Here, we assess “Kap-centric” NPC models, which postulate that Kaps participate in establishing the selective barrier. We combine biomimetic nanopores, formed by tethering Nsp1 to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 103 publications
1
16
0
Order By: Relevance
“…We found that the decay of the number of NTRs remaining in the pore did not follow mono-exponential decay (Figure 7A), indicating the presence of more than one escape timescale. Instead, the decay is well approximated as a bi-exponential, consistent with the experimental reports of two populations of NTRs with “slow” and “fast” release timescales [32,3640]. The apparent clear separation between the “slow” and the “fast” regimes occurs because the deepening of the effective potential due to competition-induced release (Figure 7B) proceeds at a non-uniform rate: rapidly initially (as many NTRs quickly escape in the initial stages of decay), and then very slowly (as it takes the remaining NTRs longer and longer to escape from the pore).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…We found that the decay of the number of NTRs remaining in the pore did not follow mono-exponential decay (Figure 7A), indicating the presence of more than one escape timescale. Instead, the decay is well approximated as a bi-exponential, consistent with the experimental reports of two populations of NTRs with “slow” and “fast” release timescales [32,3640]. The apparent clear separation between the “slow” and the “fast” regimes occurs because the deepening of the effective potential due to competition-induced release (Figure 7B) proceeds at a non-uniform rate: rapidly initially (as many NTRs quickly escape in the initial stages of decay), and then very slowly (as it takes the remaining NTRs longer and longer to escape from the pore).…”
Section: Resultssupporting
confidence: 84%
“…Furthermore, the mechanism of competition-induced release allows us to explain previous observations of apparent “fast” and “slow” fractions of NTRs within the NPC [36, 37] and in vitro FG nup assemblies and artificial NPC mimics [32, 40]. As NTRs escape from an FG nup assembly, reduced competition between the remaining NTRs deepens the effective potential within the assembly, leading to very long escape times.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Here, we investigate LLPS of FG-Nups by carrying out coarse-grained molecular dynamics (CGMD) simulations using a one-bead-per-amino-acid (1-BPA) MD model [38][39][40]. This model has been used previously to study nuclear transport through the yeast NPC [39,[41][42][43][44][45][46] and biomimetic nanopores [47][48][49][50], and to analyze the LLPS of dipeptide repeat proteins [51]. Here, we show that several intrinsically disordered FG-Nups of the yeast NPC can phase separate into liquid-like condensates and that this phase transition is mainly driven by the highly dynamic hydrophobic FGmotifs that line the FG-Nup sequences.…”
Section: Introductionmentioning
confidence: 99%